Melastomataceae Juss. do complexo de Serras da Bocaina e de Carrancas, Minas Gerais, Brasil - Lauriano, Mateus Henrique (2020)
(Melastomataceae Juss. at “Complexo de Serras da Bocaina e de Carrancas”, Minas Gerais, Brazil). The “Complexo de Serras da Bocaina e de Carrancas (CSBC)” is composed by 12 mountains of Lavras, Itumirim, Ingaí, Itutinga, Carrancas and Minduri municipalities. This study aims to estimate the diversity of species of the family Melastomataceae in the CSBC and analyze the floristic similarity with areas of “Cerrado” and Atlantic Rainforest. The species inventory was made by consulting the collection of the ESAL, HUFU and UEC herbaria, where there are representative collections of Melastomataceae for the study area. The Virtual Reflora Herbarium was also consulted as well as SpeciesLink platform. The CSBC contains 73 species of Melastomataceae, distributed in the genera Miconia, with 33 species, Pleroma (11 spp.), Microlicia and Chaetogastra (five spp. each), Trembleya (three spp.), Cambessedesia, Fritzschia, Leandra, Pterolepis and Rhynchanthera (two spp. each), and Acisanthera , Chaetostoma, Lavoisiera, Macairea, Marcetia and Siphanthera (a single species each). The cluster analysis based on similarity demonstrated many dissimilar areas highlighting the diversity and endemism found in these different areas. A group formed by CSBC, together with Serra da Canastra and Serra de São José, all in the state of Minas Gerais, is related to Arco Canastra, and its high similarity with areas of the southern province of Espinhaço, while another group formed by Catolés, Rio de Contas and Pico das Almas, in state of Bahia, can be explained by its location in province of Chapada Diamantina. The municipality of Mucugê and the Serra Dourada State Park were more dissimilar due to geomorphological aspects and endemic species.